Gynura procumbens Adventitious Root Extract Altered Expression of Antioxidant Genes and Exert Hepatoprotective Effects Against Cadmium-Induced Oxidative Stress in Mice - Sugiharto; Dwi Winarni; Anjar Tri Wibowo; Ufairanisa Islamatasya; Idqa Nurtri Bhakti; Nabilatun Nisa; Boon Chin Tan; Yosephine Sri Wulan Manuhara (HAYATI Journal of Biosciences, 2022)
Exposure to cadmium (Cd) could increase of reactive oxygen species (ROS) and changes in expression of antioxidant genes. Gynura procumbens is a medicinal plant that is rich in phenolic and flavonoid compounds. The aimed of study to evaluate the hepatoprotective effect of G. procumbens adventitious root (GAR) extract against Cd toxicity, especially expression rate of hepatic antioxidant genes. Twenty-five male mice were treated as follows: P1 (control), P2 (Cd100mg/L), P3 (GAR100mg/L + Cd100mg/L), P4 (GAR200mg/L + Cd100mg/L), and P5 (GAR300mg/L + Cd100mg/L). The samples (blood and liver) were collected for analysis of malondialdehyde (MDA) levels, superoxide dismutase (SOD) and catalase (CAT) activities, and their relative gene expression were determined. The hematological assay showed Cd-treated administered with GAR extract increased the number of red blood cells (RBC), haemoglobin concentration (HGB), hematocrit (HCT), mean corpuscular volume (MCV), and mean corpuscular haemoglobin (MCH), but reduced the level of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). In addition, the GAR extract decreased the MDA production, but increased the activities of SOD and CAT. These enzymatic activities were positively correlated with their respective gene transcripts. Our study revealed that GAR extract administration showed marked hepatoprotective effects against Cd-induced oxidative stress.